Avaliação clínica, laboratorial e hemogasométrica de cadelas com piometra - Leonardo Dias Mam?o (2013)
Pyometra is one of the most common disorders of the surgical clinic of small animals, commonly occurs in diestrus, because hormonal actions associated with bacterial infection, leading to the production and accumulation of purulent exudate in the uterine lumen. Among the most frequent clinical signs, may be cited vaginal secretion, prostration, loss of appetite, dehydration, vomiting, polyuria, polydipsia, among others. More severe changes as renal and hepatic dysfunction, cardiac arrhythmias and electrolyte and acid-base disorders may occur due to endotoxemia. The electrolyte and acid-base imbalances are complications that may contribute to disease progression, worsening the patient's general condition, and can take to death. This study aims to characterize and evaluate, in dogs with pyometra, the electrolyte and acid-base imbalance changes, evaluate whether preoperative fluid therapy is effective in correcting these imbalances, to characterize the clinical and laboratory animals and evaluate if the standard therapy used by Veterinary Hospital /UFMG is effective in the treatment of dogs with pyometra. We studied 20 female dogs with different breed, weight and age with clinical and ultrasonographic diagnostic of pyometra. Clinical evaluation was performed, blood count, biochemical profile, urinalysis, and blood gas analysis of all animals in 8 pre-set intervals. Among the results was observed in the clinical evaluation emesis, diarrhea, anorexia, prostration, polyuria and polydipsia, dehydration, and abdominal distention in some animals evaluated. Still, the laboratory evaluation was observed anemia, leukocytosis with neutrophilia with a regenerative left shift, monocytosis, hypoalbuminemia, hyperglobulinemia, elevated liver enzymes, azotemia and hyperlactatemia in some animals. In conclusion, no changes were observed in animals with severe closed pyometra in relation to open. Also concluded that fluid therapy (ringer lactate) preoperatively was effective in the correction of metabolic acidosis, however, did not correct the metabolic alkalosis and improved the respiratory alkalosis. Although it was concluded that although during the trial period has been observed all acid-base disorders primary and two mixed disorders, the disorder was the most frequent respiratory alkalosis. It was also concluded that the therapy instituted at the Veterinary Hospital /UFMG was effective in treating animals with pyometra.